Mechanical properties of high strength reinforcing bars exposed to elevated temperatures - Zaidi, K.A.; Sharma, U.K.; Bhandari, N.M. (Journal of Structural Engineering, 2024)
This paper presents the residual mechanical properties of high yield strength rebars after exposure to high temperatures. Accurate prediction of the structural properties, particularly of steel bars exposed to high temperature, is necessary for determining the load carrying capacity of structures during and after fire. Therefore, in this context several tensile tests on steel rebars were conducted after exposing them to different temperatures ranging from ambient to 8000C and subsequently cooled. The test variables included temperature of exposure, yield strength of rebars and diameter of rebars. It was observed that the properties like ultimate strength and yield strength reduced with the increase in temperature while ultimate strain and percentage elongation increased. Influence of temperature on residual properties of reinforcing bars was evident mainly after 5000C. However, residual stiffness of rebars remained unaffected within the range of temperatures considered in this study. Based on the results, a mathematical expression for determining the residual yield strength of reinforcing bars has been proposed.